Biliary atresia in children (analytical literature review and review of own observation) - Gorbatyuk, Olga; Kurylo, Halyna; Горбатюк, Ольга Михайлівна (Wydawnictwo Aluna, 2024)
Aim: to review information resources and analysis of the own experience on this problem for the provision of modern knowledge in the pathogenesis of the pathology, the latest diagnostic and treatment technologies, with consideration of the need to adhere to a single strategy in the management of patients with BA. Materials and Methods: The analysis of the data regarding the results of existing studies evaluating the clinical benefit and safety of diagnostic and treatment methods in Biliary atresia. Conclusions: BA is the leading cause of neonatal cholestasis development. Early diagnostics of BA, based on the complex evaluation of clinical-laboratory, instrumental and morphological signs of the pathology, has a significant meaning. Surgical correction during the first 2 months of life – the Kasai procedure, as well as dynamic post-surgery follow-up significantly prolong the life of children and allow postponing liver transplantation. The highest patient survival both at the first stage of treatment - conduction of the Kasai procedure and the stage of liver transplantation may be achieved by joined work of surgeons and pediatricians, which allows considering the whole row of possible problems.
Keywords: biliary atresia; infants; diagnostics; treatment